Estilo de liderazgo del gerente general y el desempeño laboral de los trabajadores de la Empresa Jijuna Gourmet S.R.L., Cajamarca, 2025 - Huatay Novoa, Luz Maribel (2026)
El presente trabajo de investigación tuvo como objetivo determinar la influencia del estilo de liderazgo en el desempeño laboral de los trabajadores de la empresa Jijuna Gourmet S.R.L., Cajamarca, 2025.The study had a quantitative approach, a correlational level, and a non-experimental cross-sectional design. The deductive and analytical methods were employed. The population and sample consisted of 13 workers, using non-probabilistic sampling. The data collection technique used was a survey, and the instrument was a structured questionnaire with Likert-type questions. This instrument was validated by expert judgment and subjected to a reliability test through Cronbach's alpha coefficient, using SPSS software version 27.The results, according to the linear regression model, show the existence of influence between the variables, with a coefficient of determination of 0.634. Likewise, a predominantly authoritarian leadership style was identified, at 46%, followed by the democratic and laissez-faire styles. The average level of work performance was 39.83 points, according to a norm-referenced measurement scale. On the other hand, a correlation coefficient of 0.614 was obtained, with a significance level of 0.034 (p < 0.05), which indicates a positive and significant correlation. In conclusion, it was determined that the predominant leadership style of the general manager is authoritarian, the workers' level of job performance is average, and there is a significant influence between the leadership style and the job performance of the employees at Jijuna Gourmet S.R.LLiderazgo